2016
DOI: 10.1063/1.4966941
|View full text |Cite
|
Sign up to set email alerts
|

Underdense a-Si:H film capped by a dense film as the passivation layer of a silicon heterojunction solar cell

Abstract: Underdense hydrogenated amorphous silicon (a-Si:H) prepared by plasma-enhanced chemical vapor deposition was used as a passivation layer in silicon heterojunction (SHJ) solar cells. By reducing the thickness of the underdense a-Si:H passivation layer from 15 nm to 5 nm, the open circuit voltage (Voc) of the corresponding SHJ solar cell increased significantly from 724.3 mV to 738.6 mV. For comparison, a widely used transition-zone a-Si:H passivation layer was also examined, but reducing its thickness from 15 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…The sample corresponding to the maximum (C H SiH2 + C H SiH3 )/C H exhibits the highest passivation quality among the samples prepared with different T mesh and/or T sub . This suggests that using SiHx (x=2,3) -rich a-Si:H grown at low T sub as a passivation layer is advantageous to inhibit an undesirable epitaxial growth at the a-Si:H/c-Si interface, consistently with the previous studies [17,18].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The sample corresponding to the maximum (C H SiH2 + C H SiH3 )/C H exhibits the highest passivation quality among the samples prepared with different T mesh and/or T sub . This suggests that using SiHx (x=2,3) -rich a-Si:H grown at low T sub as a passivation layer is advantageous to inhibit an undesirable epitaxial growth at the a-Si:H/c-Si interface, consistently with the previous studies [17,18].…”
Section: Resultssupporting
confidence: 87%
“…This T mesh coincides with the T mesh corresponding to the maximum (C H SiH2 + C H SiH3 )/C H in Figure 2. This is consistent with the previous studies [17,18] which argue that use of underdense i a-Si:H with high C H SiH2 /C H SiH ratio as a passivation layer is advantageous, because a highly disordered microstructure of the material inhibits an Fig. 3.…”
Section: Passivation Quality and Structural Properties Of The A-si:h supporting
confidence: 92%
“…Furthermore, surface passivation at the a‐Si:H/c‐Si interface is strongly affected also by overlying doped (p‐ or n‐type) layers, which are necessary for collection of either electrons or holes. [ 19,29,30 ]…”
Section: Introductionmentioning
confidence: 99%
“…Such porous a-Si:H layers especially yield a superior passivation quality with ultrathin $5 nm thick layers, which is in stark contrast to dense a-Si:H for which it is commonly observed that thicker films yield a better passivation quality. 33 Thirdly, an atomically smooth a-Si:H/c-Si interface is desired, i.e., epitaxial growth should be avoided. The presence of epitaxy results in reduced levels of interface passivation, especially upon post-deposition annealing.…”
Section: Introductionmentioning
confidence: 99%